Research Anthology on Environmental and Societal Impacts of Climate Change 2022
DOI: 10.4018/978-1-6684-3686-8.ch055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climate Change on Tropical Dry Forests

Abstract: Around 1.6 billion people in the world are directly dependent on forests for food, fodder, fuel, shelter, and livelihood, out of which 60 million are entirely dependent on forests. Forests silently provide us with ecosystem services such as climate regulation, carbon sequestration, harbouring biodiversity, synchronizing nutrient cycling, and many more. Tropical Dry Forests (TDF's) occupy around 42% of total forest area of the tropics and subtropics and facilitate sustenance of world's marginalized populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Sinha (2022) studied the impact of climate change on tropical dry forests, which also included D. melanoxylon as it is amongst the key species in tropical dry deciduous forest (Kumar et al 2017). The study reported that the Western Ghats' dry deciduous forests would decline due to expected climate change (Sinha 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sinha (2022) studied the impact of climate change on tropical dry forests, which also included D. melanoxylon as it is amongst the key species in tropical dry deciduous forest (Kumar et al 2017). The study reported that the Western Ghats' dry deciduous forests would decline due to expected climate change (Sinha 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Sinha (2022) studied the impact of climate change on tropical dry forests, which also included D. melanoxylon as it is amongst the key species in tropical dry deciduous forest (Kumar et al 2017). The study reported that the Western Ghats' dry deciduous forests would decline due to expected climate change (Sinha 2022). The dry deciduous forest of central India (Madhya Pradesh and Maharashtra) is expected to become moister as temperatures and precipitation rise (Ravindranath and Sukumar 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There would be a severe decline in the extremely suitable habitat for B. monosperma in Western Ghats regions; however, it will considerably be sustained in the Nilgiri hills in southern India. According to regional studies, the dry deciduous forests of the Western Ghats may decline as a result of projected climate change (Sinha, 2022). Again, the moderately suitable habitat of B. monosperma will decrease in central India.…”
Section: Distribution Of B Monosperma In Future Climate Scenariosmentioning
confidence: 99%